Biochar de cama de frango: produção, aplicação e análise de suas propriedades no solo e no cultivo de rabanetes - Pereira, Moisés Edevaldo (Universidade Federal de São Carlos, 2024)
Brazil stands out in broiler production and is the largest exporter. In 2022 alone, Brazil produced 14.57 million tons of chicken meat. However, considerable amounts of poultry litter are also generated annually in Brazil due to the growing demand and production of broilers, causing concerns for poultry farmers such as improper disposal which can lead to environmental pollution. The aim of this study was to evaluate the production of biochar from chicken litter on a pilot scale, characterize the biochar produced, apply the biochar to the soil in a field experiment and analysis its effects on the soil and on radishes. Around 40 kg of chicken litter was collected after raising two batches of chickens. To produce biochar, around 23.5 kg of the material was subjected to the pyrolysis process, which was carried out at 450 °C, a heating rate of 20 °C min-1 and a residence time of 6 hours. The biochar parameters studied were: gravimetric yield, immediate analysis, scanning electron microscopy and energy dispersive spectroscopy. The field experiment was set up in a randomized block design with 3 replications and 5 fertilization treatments each (control, chicken litter, biochar 20 t ha-1, biochar 60 t ha-1 and commercial NPK). For the effect of the biochar on the plants, radish development parameters were analyzed (root diameter, fresh masses root and leaf, leaf height, number of leaves, dry masses root and leaf, percentage of cracked roots, number of commercial roots and productivity. For the effect of biochar on the soil, soil analyses were carried out at 3 different times (before planting, after the first planting cycle, after the second cycle radishes planting). The results of the laboratory analysis of the biochar showed that, with the larger equipment, a longer residence time was required for the material to pyrolyze completely. The gravimetric yield was 38.38%, the moisture content 4.49%, the volatile content 24.11%, the ash content 34.40% and the fixed carbon content 41.49%, which showed that chicken litter is a suitable material for producing biochars for application to the soil. The results of the field experiment showed that biochar resulted in higher radish productivity (25.17 and 28.55 t ha-1 for the 20 and 60 t ha-1 treatments, respectively), as well as better results in most of the other development parameters analyzed. In the soil, the effects of biochar were positive, implying in retention of NPK levels, unlike the other treatments, showing potential for replacing mineral and organic fertilization, both for radish development parameters and soil fertility.
Poultry litter biochar: production, application and analysis of its properties in soil and in radish cultivation
Keywords: Biochar; Cama de Aviário; Resíduos; Recuperação de Solo; Recuperação Energética; Chicken Litter; Soil Recovery; Waste; Energetic Recovery; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FISICA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::QUIMICA DO SOLO; CIENCIAS EXATAS E DA TERRA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE PROCESSAMENTO DE PRODUTOS AGRICOLAS; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO::CONSERVACAO DE SOLO E AGUA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL::NUTRICAO E CRESCIMENTO VEGETAL; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FISICO-QUIMICA ORGANICA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::CONTROLE DA POLUICAO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::QUALIDADE DO AR, DAS AGUAS E DO SOLO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::APROVEITAMENTO DE SUBPRODUTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE PRODUTOS DE ORIGEM ANIMAL; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::CARVAO; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::FERTILIZANTES; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::TRATAMENTOS E APROVEITAMENTO DE REJEITOS